DETERMINANTS OF THE INCIDENCE OF DIARRHEA IN TODDLERS AGED 12-59 MONTHS IN JAYAPURA CITY: Determinan Kejadian Diare Pada Balita Usia 12-59 Bulan di Kota Jayapura - Irmanto, Maxsi; Irjayanti, Apriyana; Fatiah, Mona Safitri; Ilmidin, Ilmidin (Jurnal Berkala Epidemiologi, 2025)
Background:  Diarrhea in toddlers can be more deadly compared to other ages because the percentage of fluid in the baby’s body is greater. In 2023, data from 14 health centers in Jayapura City showed that diarrhea consistently ranked among the top 10 diseases, particularly at Abepura and North Jayapura Health Centers. Purpose:  This study aims to analyze the determinants of diarrhea incidence, including risk factors, among toddlers in Jayapura City. Methods:  A cross-sectional design was applied with a sample of 192 toddlers aged 12–59 months selected through accidental sampling. Inclusion criteria were mothers of toddlers aged 12–59 months, residing in the community health center working area, and willing to participate. Exclusion criteria included toddlers with congenital or chronic diseases, mothers not serving as primary caregivers, and uncooperative respondents. Data were collected using questionnaires and processed with SPSS software. Univariate and bivariate analyses employed the chi-square test, while multivariate analysis used multiple logistic regression.   Results:  Exclusive breastfeeding (p = 0.00) and maternal attitude (p=0.01) were significantly related to diarrhea incidence. Exclusive breastfeeding was identified as the main determinant, with p = 0.00 and an Exp(B) value of 4.32. Conclusion:  Exclusive breastfeeding is the key determinant of diarrhea incidence among toddlers aged 12–59 months in Jayapura City.